Borneodendron aenigmaticum - Khoo, E.; Colin Ruzelion Maycock; Damit, A.; Nilus, R.; Sugau, J.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
The species is endemic to Sabah. It is found growing in primary forest that occurs on ultramafic substrates. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 56 km2 and 8,777.8 km2 respectively. Although the AOO is calculated from known existing records, it is considered that the actual AOO may be considerably larger than this due to under sampling. There are no records of habitat decline for the species as ultramific areas are protected in Sabah. Therefore, the species occurs in nine Totally Protected Areas and no direct threats impact the species. Hence, it is assessed as Least Concerned. The species is endemic to Sabah, it is known to occur on ultramafic substrates.